To study the e-banking on effectiveness among Senawang Specialist Hospital (SALAM) staff / Nazihah Othman and Siti Nurhaziqah Qadirah Shaikh Norsham - Othman, Nazihah; Shaikh Norsham, Siti Nurhaziqah Qadirah (Faculty of Business and Management, 2014)
This study designed to study the effectiveness of e-banking towards customer. The research consists of three factors in this study which is security of e-banking, acceptance of e-banking and service of e-banking. For this study, only 50 of respondents which are most of them are employees from private sectors at Senawang Specialist Hospital (SALAM). They were selected as respondents for this study. The objectives of this study aim to identify whether the electronic banking services are effective towards customers convenience and to evaluate whether the factor that influence customer satisfaction toward electronic banking. This study also takes the consideration of the customers of ease of use the e-banking by depends on three factors involve. Besides, this study quantitative research whereby the findings of the study were analyzed by using Statistical Package for the Social Science (SPSS).